METODE SELF TALK UNTUK MENINGKATKAN KESADARAN DIRI SANTRI TAHFIDZUL QUR’AN PONDOK PESANTREN DARUSSALAM BLOKAGUNG BANYUWANGI - agung obianto (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2021)
Self-talk is part of Rational Emotive Behavior Therapy (REBT). Self-talk is one of the techniques in REBT theory, which is a way of repeating positive words or expressions that are adapted to the circumstances of each individual for a certain time. The self-awareness is when a person can realize the emotions that are descending on his mind due to the problems that are being faced so that he can then control himself. The problems that we examine in this thesis are: 1) How is the self-awareness of the students of tahfidzul quran Islamic boarding school Darussalam Blokagung Banyuwangi? 2) What forms of self talk are used by tahfidzul qur'an students to foster self-awareness in the Darussalam Islamic boarding school Blokagung?. Which aims to determine self-awareness and the form of self-talk used in an effort to foster the spirit of memorizing the Qur'an. In answering these problems, the researchers used a qualitative method that was useful to find out the lack of self-awareness of the students of the Darussalam Islamic boarding school Blokagung in memorizing the Koran. Indicators carried out by researchers are interviews with caregivers, administrators and several students involved. Also using the documentation and data that has been made by the administrators of the tahfidzul quran Islamic boarding school Darussalam Blokagung. From the results of the study, it can be concluded that the Darussalam Islamic boarding school Blokagung precisely in the Syafa'atul Qur'an dormitory has less self-awareness of its responsibilities as tahfidzul Qur'an students. And with the positive method of rational self-talk to help informants not to give up easily and keep trying to achieve an expected goal.